Insights into the lived experience of Long-Term Care and End of Life Transitions in Malta - Christian, Borg Xuereb (Magyar Gerontológia, 2023)
In this keynote presentation, I explore the profound implications of the global demographic shift towards an ageing population. I delve into the challenges and opportunities presented by this shift, using Malta as a unique case study with 25% of its citizens aged 60 and older. The dense population poses challenges for infrastructure, healthcare access, and the overall well-being of older individuals.